ISLAMIC BANK ASSET GROWTH: PREDICTIVE ASSESSMENT TOWARD DOMINANT VARIABLES AFFECTING - Dermawan, Dorry; Hunainah, Hunainah; Suseno, Bambang Dwi; Basrowi, Basrowi (Universitas Airlangga, 2021)
This study departs from asset growth in Islamic banks which has decreased in the last four years even though assets have increased every year. This research is structured to be the basis for making policies to increase the growth of assets of Islamic banks. The research design used is quantitative with the help of smart PLS ver.3.3. The number of samples is 94 people from a population of 123 employees of Islamic Banks Serang and Cilegon Branch Offices with supervisory positions and above. The sample selection in this study uses probability sampling, so that all branch offices of Islamic banks in Cilegon and Serang as well as all supervisory work units have the same opportunity to be selected as samples. The results indicate that the ones that have the biggest influence in increasing the growth of Islamic bank assets are the financing to deposit ratio and non-performing financing. This can be seen from the path coefficient value resulting from this study between financing to deposit ratio on asset growth has a coefficient value of 2.818 and non-performing financing on asset growth has a coefficient value of 3.767. Thus, both financing to deposit ratio and non-performing financing influence increasing the growth of assets of Islamic banks. The results of this study emphasize to bankers to maintain the quality of financing to remain smooth and avoid non-performing financing.